2014
DOI: 10.1179/2045772314y.0000000258
|View full text |Cite
|
Sign up to set email alerts
|

Upper limb joint kinetics of three sitting pivot wheelchair transfer techniques in individuals with spinal cord injury

Abstract: Study design: Repeated measures design.Objective: This study compared the upper extremity (UE) joint kinetics between three transfer techniques. Setting: Research laboratory. Methods: Twenty individuals with spinal cord injury performed three transfer techniques from their wheelchair to a level tub bench. Two of the techniques involved a head-hips method with leading hand position close (HH-I) and far (HH-A) from the body, and the third technique with the trunk upright (TU) and hand far from body. Motion analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
(33 reference statements)
0
16
0
1
Order By: Relevance
“…Each of the lower limbs joint is responsible for the individual steps of human movement [16]. The effects of forces and moment of forces acting at the joints were determined based on the free-body diagram and inertial force diagram of lower limb as shown in Figure 2 and The process by which the reaction forces and muscles moment are calculated is called link segment modelling [10]. The full kinematic of the lower limb and the anthropometric data of the subject and external and ground forces, will allow the determination of the load joint by computing the forces acting on the link segment model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the lower limbs joint is responsible for the individual steps of human movement [16]. The effects of forces and moment of forces acting at the joints were determined based on the free-body diagram and inertial force diagram of lower limb as shown in Figure 2 and The process by which the reaction forces and muscles moment are calculated is called link segment modelling [10]. The full kinematic of the lower limb and the anthropometric data of the subject and external and ground forces, will allow the determination of the load joint by computing the forces acting on the link segment model.…”
Section: Methodsmentioning
confidence: 99%
“…Inverse dynamics is a technique of computing joint reaction forces and moments in a multi-body system by using measured kinematics and external forces [7]. This technique was used in biomechanical analysis to calculate joint loads and muscle forces in both upper [8][9][10] and lower limbs [1][2][3][4][5][11][12]. Elliott et al reported the effects of various tennis serving techniques on the shoulder and elbow joint loads.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, lower scores on the TAI were associated with increases in forces, moments, and the rates of loading at the wrists, elbows, and shoulders. Many of the same skills that these Veterans were lacking have been directly linked with awkward motions and higher forces and moments [29,[44][45]. These skill deficits combined with the repetitious nature of transfers (upward of 40 times per day [4]) may help explain why the prevalence of upper-limb pain and injuries are so high among Veterans with SCI [14][15].…”
Section: Transfer Skill Deficitsmentioning
confidence: 99%
“…Veterans could also score a "no" on this item if they reached too far outside their base of support to attain a handgrip. Knowing where best to place the hands relative to the body is a skill that is very important for reducing forces and effort [29,45].…”
Section: Relationship Between Subjects' Characteristics and Transfermentioning
confidence: 99%
“…It has been suggested that proper technique may reduce progression of shoulder pathology despite high usage. Wheelchair athletes have fewer hospitalizations and no greater incidence of shoulder pathology [70], and focal strengthening of target muscles [71] and optimal maneuver techniques [72] can be vital in preventing shoulder injury. While increased mechanical stressing of muscles and bones of the shoulder are well correlated to pathology, methodologies to identify user-speciic movement training paterns to mitigate injury progression are lacking.…”
Section: Identifying Optimal Movements From Individual Physiologymentioning
confidence: 99%